2004
DOI: 10.1556/abiol.55.2004.1-4.35
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Metamorphosis in the Marine GastropodIlyanassa obsoleta: 5HT, NO and Programmed Cell Death

Abstract: Abstract:The central nervous system (CNS) of a metamorphically competent larva of the caenogastropod Ilyanassa obsoleta contains a medial, unpaired apical ganglion (AG) of approximately 25 neurons that lies above the commissure connecting the paired cerebral ganglia. The AG, also known as the cephalic or apical sensory organ (ASO), contains numerous sensory neurons and innervates the ciliated velar lobes, the larval swimming and feeding structures. Before metamorphosis, the AG contains 5 serotonergic neurons a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 35 publications
(45 reference statements)
2
46
0
Order By: Relevance
“…For instance, Robertson and colleagues reported that NO regulates tactile learning (Robertson et al, 1994) and visual learning (Robertson et al, 1996) processes in Octopus vulgaris. It was also found that NO is involved in regulating neural transmissions to intestinal muscles of the common snail Helix lucorum (Röszer et al, 2004) and in the fine olfactory discrimination of the terrestrial slug Limax valentianus (Sakura et al, 2004), and, importantly, it was found that NO plays a crucial role in regulating metamorphosis of the marine snail Ilyanssa obsolete (Leise et al, 2004). In the present study, the involvement of NO and the associated cGMP signaling pathway during larval settlement of B. amphitrite were investigated.…”
Section: Discussionmentioning
confidence: 77%
“…For instance, Robertson and colleagues reported that NO regulates tactile learning (Robertson et al, 1994) and visual learning (Robertson et al, 1996) processes in Octopus vulgaris. It was also found that NO is involved in regulating neural transmissions to intestinal muscles of the common snail Helix lucorum (Röszer et al, 2004) and in the fine olfactory discrimination of the terrestrial slug Limax valentianus (Sakura et al, 2004), and, importantly, it was found that NO plays a crucial role in regulating metamorphosis of the marine snail Ilyanssa obsolete (Leise et al, 2004). In the present study, the involvement of NO and the associated cGMP signaling pathway during larval settlement of B. amphitrite were investigated.…”
Section: Discussionmentioning
confidence: 77%
“…The neurotransmitters dopamine and serotonin typically have opposing effects on swimming and metamorphosis of molluscan larvae (Leise et al, 2004;Braubach et al, 2006;Yamamoto et al, 1999;Zega et al, 2005). Larvae were exposed to the dopamine precursor L-DOPA and to serotonin by diluting stock solutions to final concentrations of 10 ; assays were performed in the dark to prevent photochemical degradation of L-DOPA.…”
Section: Pharmacological Manipulation Of Spontaneous Metamorphosismentioning
confidence: 99%
“…Because exogenous 5-HT can elicit metamorphosis, presumably by mimicking the action of serotonergic neurons (Couper and Leise, 1996;Leise et al, 2001), we anticipate that 5-HT will potentiate larval responses to natural inducers. Conversely, because nitric oxide inhibits metamorphosis in competent larvae (Froggett and Leise, 1999;Leise et al, 2004;Hens et al, 2006), we expect this diatom inducer to antagonize this activity.…”
Section: Coscinodiscus Sp Elicits Metamorphosismentioning
confidence: 99%
“…When larval metamorphosis is initiated by the reception of an appropriate pharmacological stimulus in the laboratory, the ensuing morphological and physiological transformations include a decrease in the expression of the gene coding for nitric oxide synthase, the enzyme that produces NO (Froggett and Leise, 1999;Leise et al, 2001Leise et al, , 2004Gifondorwa and Leise, 2006;Hens et al, 2006). Leise and colleagues also confirmed Levantine and Bonar's (1986) discovery that the classical neurotransmitter serotonin (5-HT) can induce metamorphosis in competent larvae, and they provided pharmacological data supporting the idea that exogenously applied 5-HT mimics the action of serotonergic neurons in the larval nervous system (Couper and Leise, 1996;Leise et al, 2001Leise et al, , 2004. Our studies of the cellular and physiological mechanisms that bring about metamorphosis in this species continue, but to understand the regulation of this process from an environmentally relevant viewpoint, we need specific knowledge of how I. obsoleta reacts to a natural inducer.…”
Section: Introductionmentioning
confidence: 99%